حرية القاضي الجنائي في تكوين عقيدته - نور الهدى مرايسية (My University, 2021)
Abstract: In this note, we discussed the principle of the criminal judge’s freedom to form his faith as one of the most important legal principles on which the free evidence system is based, especially since this principle is of a practical nature, and the Algerian legislator took it due to its importance and appreciation, which means that the criminal judge has the freedom to determine the evidence Its persuasive value, as he may take any evidence he is comfortable with from any source he wishes, whether in the preliminary investigations or in the court sessions, so he has the authority to assess the evidence presented to him and to give preference to some of them over the others, and whether the evidence is direct and leads by itself to the conclusion that the judge reached, Or was it indirect evidence by which the judge reaches his conviction after making a practical effort based on observing the facts and thinking about them in order to arrive at the truth, then he is free to assess the accused’s confession, the statements of witnesses, documents, judicial evidence and experience, so he determines the value of each evidence in proof according to his conviction But the fear of the criminal judge slipping into control, given that he enjoys the freedom of self-conviction that is not, in principle, subject to any external control, except for the control of conscience, which cannot be subject to any external oversight. Freedom that must be specific and has its correct specific framework that ensures it achieves its goal - reaching the truth - without deviating from its path and heading to control and tyranny, so the law has drawn for it the limits that it must be within and it is not permissible to deviate from it. ................ ملخص المذكرة تناولنا في هذه المذكرة مبدأ حرية القاضي الجنائي في تكوين عقيدته باعتباره من أهم المبادئ القانونية التي يقوم عليها نظام الإثبات الحر، خاصة وأن هذا المبدأ يتسم بالطابع العملي، وقد أخذ به المشرع الجزائري نظرا لأهميته، والذي يعني أنّ القاضي الجنائي له الحرية في تحديد الأدلة وتقدير قيمتها الإقناعية، فله أن يأخذ بأي دليل يرتاح إليه من أي مصدر شاء سواء في التحقيقات الأولية أو في جلسات المحاكمة فيملك سلطة في تقدير الأدلة المطروحة عليه وفي ترجيح بعضها على البعض الآخر وسواء كان الدليل مباشرا مؤديا بذاته إلى النتيجة التي انتهى إليها القاضي أم كان دليلا غير مباشر يتوصل بواسطته القاضي إلى تكوين اقتناعه بعد بذل مجهود عملي يقوم على ملاحظة الوقائع والتفكير فيها للوصول إلى الحقيقة، فله حرية تقدير اعتراف المتهم، أقوال الشهود المحررات، القرائن القضائية والخبرة، فيحدّد قيمة كل دليل منها في الإثبات وفقا لقناعته. ولكن الخوف من انزلاق القاضي الجنائي نحو التحكم بالنظر إلى أنه يتمتع بحرية اقتناع ذاتية لا تخضع من حيث المبدأ إلى أي رقابة خارجية، إلّا رقابة الضمير الذي لا يمكن إخضاعه لأي رقابة خارجيّة، الأمر الذي دفع بالمشرع على أن يتدخل بالحدّ الممكن لوضع ضوابط واستثناءات لهذه الحرية التي لا بد أن تكون محدّدة ولها إطارها المحدّد الصحيح الذي يكفل لها تحقيق الهدف منها الوصول إلى الحقيقة دون أن تنحرف عن مسارها وتتجه إلى التحكم والاستبداد ، لذلك رسم لها القانون الحدود التي يجب أن تكون ضمنها ولا يجوز الخروج عنها. ................. RÉSUMÉ : Dans ce mémorandum, nous avons abordé le principe de la liberté du juge pénal de former sa croyance comme l’un des principes juridiques les plus importants sous-tendant le libre système de la preuve. Ce principe est de nature pratique et a été adopté par la législation algérienne en raison de son importance. ce qui signifie que le juge pénal est libre de déterminer la preuve et d’en évaluer la valeur persuasive, il a le pouvoir d’évaluer la preuve dont il est saisi et de se peser les uns les autres. Que la preuve soit directe en elle-même conduit à la conclusion du juge ou à la preuve indirecte par laquelle le juge peut former sa condamnation après un effort pragmatique pour observer et réfléchir sur les faits afin d’obtenir la vérité, les aveux, les déclarations écrites des témoins, la preuve judiciaire et l’expérience, en déterminant la valeur de chaque preuve en preuve selon sa condamnation. Mais la crainte de la descente du juge pénal dans le contrôle, car il jouit d’une liberté de la auto-condamnation n’est, en principe, soumise à aucun contrôle externe. Seule la censure d’une conscience qui ne peut être soumise à aucune censure extérieure, a incité le législateur à intervenir dans la mesure du possible pour établir des contrôles et des exceptions à cette liberté, qui doit être défini et qui dispose du cadre spécifique approprié pour garantir qu’il atteigne son objectif d’atteindre la vérité sans être déraillé et tendu au contrôle et à la tyrannie. s droits ", la loi a donc défini les limites dans lesquelles ils doivent et ne peuvent pas être dérogés.